Features of aura in paediatric migraine diagnosed using the ICHD 3 beta criteria. (October 2018) - Balestri, Martina; Papetti, Laura; Maiorani, Daniela; Capuano, Alessandro; Tarantino, Samuela; Battan, Barbara; Vigevano, Federico; Valeriani, Massimiliano
Background: In children and adolescents, the prevalence rate of migraine with aura is 1.6%. Few studies concerning migraine with aura features in paediatric population have been reported. Aim: The aim of our study was to investigate clinical features of aura in a retrospective cohort of children with migraine with aura. Furthermore, we studied whether the International Classification of Headache Disorder (ICHD) 3 beta version criteria could efficiently detect migraine with aura in a paediatric population. Results: We included 164 patients who experienced aura associated with headache (mean age 9.92 ± 2.64 years). When the ICHD-II criteria were used, a final diagnosis of migraine with typical aura was obtained in 15.3% of patients, probable migraine with typical aura in 13.4%, and typical aura with headache in 61.8%, while in in 9.5% of patients the diagnosis was undetermined. According to ICHD-3 beta, we diagnosed migraine with typical aura in 77.7% of patients, probable migraine with typical aura in 13.4%, and an undetermined diagnosis in 9.5% (less than two attacks). Conclusion: Aura features did not depend on age and were similar to those of adults. However, the headache could be difficult to classify if headache duration was considered. In this view, the ICHD-3 beta offers the advantage of not considering headache features, including pain duration, for the diagnosis of migraine with typical aura, thus making this diagnosis easier in children and adolescents.